1990
DOI: 10.1038/hdy.1990.26
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of competitive interactions in triocultures of Drosophila melanogaster

Abstract: Competitive interactions in complex mixtures of genotypes have rarely been studied despite their obvious importance in both natural and commercial populations. Here, we describe a procedure for the analysis of competition in tripartite mixtures of Drosophila melanogaster genotypes. We have utilised a substitution design coupled with a yield-density regression analysis which describes intra- and inter-genotypic competitive effects in terms of simple linear parameters. The experimental design allows any of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Thus, we find the surprising outcome that competition can lead to long‐term maintenance of heritable variation for traits under constant directional selection, but those traits may never show an actual evolutionary response to selection. We suggest that competition dependence of fitness‐related traits may be common in nature because of evidence for both genetic interactions for competitive success (e.g., Hemmat and Eggleston 1989; De Miranda et al 1991; Colegrave 1993) and condition‐dependent expression of traits (e.g., Bakker et al 1999; David et al 2000; Holzer et al 2003). However, empirical investigation is required to confirm this.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, we find the surprising outcome that competition can lead to long‐term maintenance of heritable variation for traits under constant directional selection, but those traits may never show an actual evolutionary response to selection. We suggest that competition dependence of fitness‐related traits may be common in nature because of evidence for both genetic interactions for competitive success (e.g., Hemmat and Eggleston 1989; De Miranda et al 1991; Colegrave 1993) and condition‐dependent expression of traits (e.g., Bakker et al 1999; David et al 2000; Holzer et al 2003). However, empirical investigation is required to confirm this.…”
Section: Discussionmentioning
confidence: 96%
“…However, the degree to which such interactions are prevalent in natural populations remains an empirical problem and the generality of whether competitive hierarchies evolve to be transitive or nontransitive in nature is not well known. For example, there is experimental evidence that three‐way genetic competitive interactions can be significant and complex (e.g., Castro et al 1985; Hemmat and Eggleston 1989), and may exhibit negative frequency dependence (Adell et al 1989). In contrast, there is a much larger body of literature examining competitive transitivity in interspecific interactions, which has demonstrated that such a pattern of nontransitivity may be relatively common, but it is obviously unclear the extent to which patterns from interspecific competition are mirrored at the intraspecific level.…”
Section: Discussionmentioning
confidence: 99%